Soil properties considering pH-values, total nitrogen and carbon content of soil samples, and soil type determination based on sand, silt, clay composition at the Hordorf (Central Germany) groundtruthing sites - Marco Pohle; Robert Milewski; Ulrike Werban; Helko Kotas (PANGAEA, 2021)
The data set contains the results of laboratory examination of 13 soil samples taken at the ground truthing reference sites during the flight campaign.
In: Rebmann, Corinna; Lausch, Angela; Schulz, Gundula; Chabrillat, Sabine; Milewski, Robert; Schrön, Martin; Werban, Ulrike; Pohle, Marco; Schmidt, Andreas; Pohl, Felix; Hermanns, Floris; Steigerwald, Sophie; Kotas, Helko; Gimper, Sebastian; Schmidt, Patrick; Schoßland, Andreas; Lehmann, Steffen; Schütze, Claudia (2021): Remote sensing event campaign with various optical and thermal sensors for soil moisture and evapotranspiration derivation in Central Germany investigating possible effects of different spatial scales [dataset bundled publication]. Helmholtz Centre for Environmental Research - UFZ, PANGAEA, https://doi.org/10.1594/PANGAEA.931767